Long noncoding RNA uc007nnj.1 mediates neuronal death induced by retinal ischemia/reperfusion in mice via the miR-155-5p/Tle4 axis - Yuqing Feng; Jinfang Lu; Xujun Peng; Yanni Ge; Ran Zhang; Huiling Li (BMC, 2023)
Abstract Background Retinal ganglion cells (RGCs) apoptosis is a vital manifestation of retinal ischemia/reperfusion (I/R) injury, yet the underlying mechanisms are not well understood. The contribution of long noncoding RNAs (lncRNAs) to this cellular process is currently being explored. Based on a lncRNA chip assay, we aimed to investigate the role of lncRNA uc007nnj.1 in the pathological process of ischemia-induced RGCs apoptosis. Methods Hank's balanced salt solution containing 10 µM antimycin A and 2 µM calcium ionophore for 2 h to construct an ischemic model in RGCs, and elevation of intraocular pressure to 120 mm Hg for 1 h was used to construct a mouse model of retinal I/R injury. Results In this study, lncRNA uc007nnj.1 was highly upregulated in response to I/R injury in RGCs and mouse retinas. In addition, lncRNA uc007nnj.1 knockdown reduced retinal neuronal cell apoptosis in vitro and in vivo and significantly improved retinal function. Discussion Mechanistically, the results demonstrated that lncRNA uc007nnj.1 acts as ceRNA competitively binding miR-155-5p, thereby enhancing the expression levels of Tle4, thus aggravating ischemia-related apoptosis in RGCs. Conclusions Finally, our study identifies the lncRNA uc007nnj.1/miR-155-5p/Tle4 axis as a potential target for the prevention of I/R-induced retinal neuronal death.